The Effectiveness of Instagram Advertising Content on Al-Waliy Honey Gummy MSME Products Using AIDA Model Approach - Sumadinata, Raden Fathia Nurul Fadhilah; Fatimah, Sri; Hapsari, Hepi; Budiman, Muhammad Arief (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Instagram is now used as a marketing communications medium by MSMEs, including Al-Waliy Honey Gummy, which previously only went by word of mouth marketing and was still not widely known to the public. This research aims to determine the effectiveness of Instagram advertisement video created by Al-Waliy Honey Gummy MSME using the AIDA Model approach. The research design uses descriptive quantitative design with survey and interview techniques. A sample size of 103 was drawn through purposive sampling with the criteria being active users of Instagram and have watched Al-Waliy Honey Gummy advertising video on Instagram. The findings indicate that the Al-Waliy Honey Gummy advertisment is considered effective, with scores of 3,99 for attention, 4,30 for interest, 4,06 for desire, and 4,12 for action (out of 5). The study suggests a need to enhance the quality of advertisement content to elevate effectiveness from effective to very effective and become more active in promoting the products by optimizing Instagram’s features.Keywords: advertisement effectiveness, AIDA Model, Al-Waliy Honey Gummy, Instagram